Effect of diarylpentanoid analogues on lipopolysaccharide-induced interleukin-6 and interleukin-8 gene expression in airway inflammation - Liew, Kong Yen; Rosly, Nur A'dilah; Abas, Faridah; Leong, Sze Wei; Israf Ali, Daud Ahmad; Tham, Chau Ling (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2019)
Introduction: Airway inflammation is the pathological hallmark of chronic inflammatory airway diseases, especially asthma and chronic obstructive pulmonary disease (COPD). Airway epithelium plays an indispensable role in these diseases by secreting inflammatory mediators and cytokines in response to foreign substances, such as lipopolysaccharide (LPS). Previous studies have shown that diarylpentanoid analogues, especially 5-(3,4-dihydroxyphenyl)-3-hy-droxy-1-(2-hydroxyphenyl)penta-2,4-dien-1-one (DHHPD) and 2-benzoyl-6-(3,4-dihydroxybenzylidene)cyclohex-en-1-ol (BDHBC), significantly inhibited nitric oxide (NO) production; suggesting their anti-inflammatory property. However, the therapeutic potential of DHHPD and BDHBC in airway inflammation has not been explored. Thus, this study aims to investigate their effects on interleukin (IL)-6 and IL-8 gene expression in LPS-induced Calu-3 cells, a cellular model of human airway epithelium. Methods: MTT cytotoxicity assay was carried out to identify non-cytotoxic concentrations of DHHPD and BDHBC on Calu-3 cells. RT-PCR was done to determine IL-6 and IL-8 gene expression levels. Results: DHHPD and BDHBC were not cytotoxic on Calu-3 cells up to 200μM. Four non-cytotoxic concentrations were chosen – 6.25, 12.5, 25 and 50μM to determine the effect of both compounds on gene expression. All four concentrations of DHHPD and BDHBC significantly inhibited LPS-induced mRNA expression of IL-6 while all concentrations of BDHBC, except 6.25μM, significantly reduced IL-8 mRNA expression. Similar finding was obtained for DHHPD, except that at 50μM, there was no inhibition of IL-8 mRNA expression. Conclusion: Diarylpentanoid analogues, DHHPD and BDHBC, are proven to be effective in suppressing LPS-induced IL-6 and IL-8 gene expression. However, further studies are required to confirm their inhibitory effects on the production of pro-inflammatory cytokines.